Acute changes in forearm vascular compliance during transient sympatho‐excitation. Issue 8 (19th April 2022) - Olver, T. Dylan; Badrov, Mark B.; Allen, Matti D.; Coverdale, Nicole S.; Shoemaker, J. Kevin
Abstract: The study of vascular regulation often omits important information about the elastic properties of arteries under conditions of pulsatile flow. The purpose of this study was to examine the relationship between muscle sympathetic nerve activity (MSNA), vascular bed compliance, and peripheral blood flow responses in humans. We hypothesized that increases in MSNA would correlate with reductions in vascular compliance, and that changes in compliance would correspond with changes in peripheral blood flow during sympatho‐excitation. MSNA (microneurography), blood pressure (Finopres), and brachial artery blood flow (Doppler ultrasound), were monitored in six healthy males at baseline and during the last 15 s of voluntary end‐inspiratory, expiratory apneas and 5 min of static handgrip exercise (SHG; 20% maximum voluntary contraction) and 3 min of post‐exercise circulatory occlusion (SHG + PECO; measured in the non‐exercising arm). A lumped Windkessel model was employed to examine vascular bed compliance. During apnea, indices of MSNA were inversely related with vascular compliance, and reductions in compliance correlated with decreased brachial blood flow rate. During SHG, despite increased MSNA, compliance also increased, but was unrelated to increases in blood flow. Neither during SHG nor PECO did indices of MSNA correlate with forearm vascular compliance nor did vascular compliance correlate with brachial flow. However, during PECO, a linear combination of blood pressure and total MSNA was correlated with vascular compliance. These data indicate the elastic components of the forearm vasculature are regulated by adrenergic and myogenic mechanisms during sympatho‐excitation, but in a reflex‐dependent manner. Abstract : During apnea, increases in sympathetic nerve activity were related to reductions in vascular compliance, with such reductions impeding flow rate. During post‐exercise circulatory occlusion, both sympathetic factors and blood pressure appeared to modulate vascular compliance (data not shown in graphical abstract). Vascular compliance appears to be regulated by adrenergic and myogenic mechanisms during sympatho‐excitation, but in a reflex‐dependent manner.